2009
DOI: 10.4049/jimmunol.0900419
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Unusual NK Cell Responses to HIV-1 Peptides Are Associated with Protection against Maternal-Infant Transmission of HIV-1

Abstract: Most infants exposed to HIV-1 in utero and at delivery do not acquire infection. We show that mothers and infants who have CD3-negative cells that respond to HIV-1 peptides are substantially less likely to transmit and acquire infection, respectively. The CD3-negative cells, shown to be NK cells, respond with remarkable specificity and high magnitude to HIV-1 peptides from Env (envelope) and Reg (regulatory) protein regions, as measured by a whole blood intracellular cytokine assay only in the context of HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 22 publications
(22 reference statements)
4
65
0
Order By: Relevance
“…Our studies described above detecting NK cell activation in response to HIV-1 peptides in whole blood are in line with previous reports (9,27,30,31). However, previous studies have come to different conclusions regarding the mechanisms responsible for these HIV-1-specific NK cell responses (27,29).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Our studies described above detecting NK cell activation in response to HIV-1 peptides in whole blood are in line with previous reports (9,27,30,31). However, previous studies have come to different conclusions regarding the mechanisms responsible for these HIV-1-specific NK cell responses (27,29).…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, recent studies suggested that these responses are mediated by antibodies (27) and can mediate sufficient immune pressure to drive viral escape by the selection of sequence mutations (8). However, studies by different groups have resulted in different conclusions regarding the precise mechanism by which NK cells recognize HIV-1 antigens and whether these responses are mediated through CD16 or other NK cell receptors, such as killer immunoglobulin-like receptors (KIR) (27,29,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, other groups have also reported HIV-specific NK cell activation in reaction to HIV-peptide stimulation. 17,18 The mechanism of activation of NK cells by exogenous HIV peptide ADCC epitopes is investigated in this manuscript. In order for ADCC activity to occur, three key components are generally required, namely: (1) target cells that express the HIV antigen, (2) antibodies that bind the viral antigen and (3) effector cells expressing Fcγ receptors, such as NK cells, which bind the Ag-Ab complex.…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies against non-Env targets have been shown to mediate ADCC. [55][56][57][58] Yet, because Gag is not expressed on the surface of infected cells, it is unclear whether these antibodies contribute to direct lysis of infected cells or whether these antibodies act as surrogates of a more potent humoral immune profile. Along these lines, subjects who selectively generate elevated Gag-specific antibodies also generate the more abundant gp120-IgG3 antibody subclass, known to have the greatest antiviral activity.…”
mentioning
confidence: 99%